2018
DOI: 10.1080/20008686.2018.1439215
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibodies against flaviviruses, Babanki virus, and Rift Valley fever virus in Ugandan bats

Abstract: Introduction: A number of arboviruses have previously been isolated from naturally-infected East African bats, however the role of bats in arbovirus maintenance is poorly understood. The aim of this study was to investigate the exposure history of Ugandan bats to a panel of arboviruses. Materials and methods: Insectivorous and fruit bats were captured from multiple locations throughout Uganda during 2009 and 2011–2013. All serum samples were tested for neutralizing antibodies against West Nile virus (WNV), yel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 22 publications
7
37
1
1
Order By: Relevance
“…Bat ID 1740 developed neutralizing antibodies with titers between 1:160 and 1:1920 from day 7 onwards until the end of the experiment at 31 dpi, indicating a protective mechanism against RVFV replication. This is in accordance with recent findings of neutralizing antibodies in Rousettus aegyptiacus bats as well as minor epauletted fruit bats ( Epomophorus minor ) from Uganda [38]. However, no virus shedding via excretions such as saliva, feces, or urine was observed using this vaccine strain.…”
Section: Discussionsupporting
confidence: 92%
“…Bat ID 1740 developed neutralizing antibodies with titers between 1:160 and 1:1920 from day 7 onwards until the end of the experiment at 31 dpi, indicating a protective mechanism against RVFV replication. This is in accordance with recent findings of neutralizing antibodies in Rousettus aegyptiacus bats as well as minor epauletted fruit bats ( Epomophorus minor ) from Uganda [38]. However, no virus shedding via excretions such as saliva, feces, or urine was observed using this vaccine strain.…”
Section: Discussionsupporting
confidence: 92%
“…The virus sequence in this study showed a similarity to BBKV of 98-99.8% [188]. In Uganda also, the virus was isolated in two wild bats from a study of 323 bats caught from various locations in the country [189].…”
Section: Togaviridaesupporting
confidence: 53%
“…Oelofsen & Van der Ryst (1999) examined 350 samples from 150 field-caught bats in Africa, yet none were positive for antigen by use of ELISA [27]. Kading et al (2018) detected neutralizing antibodies against RVFV in Egyptian rousette bats and little epauletted fruit bats ( Epomophorus labiatus ) in Uganda, a country that has recently experienced human cases of RVFV [29,30]. Whether or not bats serve as a reservoir of RVFV during interepidemic periods remains to be determined.…”
Section: Members Of the Order Bunyaviralesmentioning
confidence: 99%
“…DENV nucleic acid and anti-DENV antibodies have been detected in Mexican bats on the Gulf and Pacific coast, and nucleic acid has been detected in the liver and/or sera of wild-caught bats in French Guiana [62,63]. Anti-DENV antibodies have been detected in multiple bat species in Uganda [29]. However, a survey in Central and Southern Mexico analyzing 240 individuals representing 19 bat species by RT-PCR resulted in no detection of viral nucleic acid [64].…”
Section: Members Of the Family Flaviviridaementioning
confidence: 99%